FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KANTOR AKUNTAN PUBLIK PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Wijaya, I Gusti Kade Harta Kesuma; Sudarma, Made (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this research is to know about factors that influence the change of Public Accounting Firm on manufacture companies in Indonesia. This research has examined  five variables:  reputation of the company (ROA), debt-to-equity ratio (DER), manipulation income (MANIP), audit fees (FEE) and the size of company (ASSET). The population in this research  are manufacture companies listed in Indonesia Stock Exchange in 2007-2012. The sampling method is purposive sampling method. There are 107 were included in the sample criteria for 5 years, which the total is 535 samples. Based on the result of logistic regression test, 1 of 5 independent variables which is   size of company give effect to the change of Public Accounting Firm. While the other variables which are reputation of companies, debt to equity ratio, manipulation income and audit fees had no influence on the change of Public Accounting Firm. Keywords   : change of Public Accounting Firm, reputation of companies,  debt to equity   ratio , manipulation income , audit fees , size of companies.